Pengaruh Pendidikan Kesehatan terhadap Pengetahuan dan Sikap Remaja tentang Kekerasan Seksual di SMP N 2 Sitiung, Dharmasraya Tahun 2024 - Deviyanti, Elvina; Fitria, Reni; Enopadria, Costarin (Jurnal Ilmu Kesehatan Dharmas Indonesia, 2024)
In 2023, there were 19,593 cases of sexual violence against adolescents in Indonesia, with 9,047 victims aged 13-17 years, according to SIMFONI-PPA West Sumatra. The purpose of this study was to determine the effect of health education on adolescent knowledge and attitudes about sexual violence. This research method is pre-experimental. The population is 169 students. The research sample is 63 people. Sampling using purposive sampling technique. Statistical tests using the Wilcoxon test. A total of 32 respondents (50.8%) had sufficient knowledge before receiving Health Education. A total of 60 respondents (95.2%) had sufficient knowledge after receiving Health Education. There is an effect of Health Education on adolescent knowledge and attitudes about sexual violence at SMPN 2 Sitiung with a P value = 0.000. The school should form a special team of teachers and students in preventing sexual violence at school.